Potential for safe and efficient biofortification of maize crops with selenium in Malawi - Chilimba, Allan Dennies Colex (2011)
Selenium (Se) is an essential element for humans, which is derived primarily from dietary sources. Habitual suboptimal dietary Se intake is associated with reduced Se status and adverse health outcomes including cardiovascular disorders, impaired immune functions and some cancers. The global extent of suboptimal dietary Se intake is difficult to estimate, but is likely to be widespread where food choices are narrow, for example, in subsistence agricultural contexts. This study aimed to: (1) characterise the likely contribution of maize grain to dietary Se intake in rural Malawi; (2) test the dependency of maize grain Se concentrations on soil factors; and (3) identify agronomic methods to improve Se concentration in maize grain. 88 field sites across Malawi were sampled across Malawi in 2009 and 2010 before determining maize grain, total soil and KH2PO4-extractable soil Se concentrations by inductively coupled plasma-mass spectrometry (ICP-MS). Dietary Se intakes from other food sources were estimated from the literature. The median maize grain Se concentration in Malawi was 0.019 mg Se kg-1 (range 0.005-0.533), representing a median intake of 6.7 µg Se person-1 d-1 from maize. Suboptimal (<30 µg d-1) dietary Se intake is therefore likely to affect most of the rural population in Malawi. Maize grain Se concentration was c. 10-fold higher in crops grown on high pH (>6.5) soils (Vertisols), probably because the dominant species of Se at high soil pH Se(VI) is more available to crops than Se(IV), as evidenced by the KH2PO4-extractable soil concentrations recorded. Total soil Se concentration ranged between 0.0521 and 0.6195 mg kg-1 but provided a poor index of Se availability. The results showed that KH2PO4-extractable Se concentrations >0.01 mg kg-1 and soil pH values >6.5 produced grain Se concentrations exceeding 0.15 mg Se kg-1, a value above which rural populations in Malawi would attain adequate Se intake. Field experiments in which three Se application methods (Na2SeO4 (aq), granular compound (NPK+Se) and granular calcium ammonium nitrate (CAN+Se) were applied were conducted at up to six sites in 2008/09 and 2009/10. Application of Se significantly increased grain and stover Se concentrations and the response was approximately linear for all sites and application methods in both years (R2 >0.90). The results showed that application of Se at 5 g Se ha-1 to maize would deliver adequate intakes for much of the population in Malawi. As total plant recovery of Se ranged from 3-45%, further work is required to identify and address the sources of this variation. In more detailed experiments, the fate of applied Se was investigated at two sites using the stable 74Se isotope. Recovery of applied Se was 0.65 and 1.08 g Se ha-1 at the Chitedze and Mbawa, sites respectively, representing 6.5 and 10.8% of the applied 10 g Se ha-1 by the maize crop; 0.2 g Se ha-1 of native soil Se was also absorbed, leaving 9.35 and 8.92 g Se ha-1 unaccounted. Of the total soil and applied fertiliser Se, fertiliser-derived Se (74Se-labelled) comprised 71 and 82% of plant-Se recovery at Chitedze and Mbawa, respectively. The residual effects of Se application on grain Se in maize crops grown in the subsequent cropping season were 0.3025 and 0.5858 µg kg-1 g-1 applied Se at Chitedze and Mbawa respectively. Residual Se detected as KH2PO4-extractable Se ranged from 0.0029 to 0.106 µg kg-1 g-1 applied Se between sites. Further studies are required to quantify the amount of Se immobilised in the soil pool or lost due to leaching or volatilisation. A further experiment examined how traditional processing procedures for maize grain affected Se concentration in maize flour. At Se fertilisation levels which would increase dietary Se intake to appropriate levels, there was no evidence that traditional milling produced any significant loss of Se from maize flour. Assessment of the contribution of maize to the dietary supply of other nutrients showed that calcium concentration, and hence intake from maize, were very low. Maize grain was low also in K, Cu and Zn but provided a good source of Fe, Mg, Mn and Mo. There is a need to monitor the concentrations of trace metals such as Cd, Co, Ni and Cr as these might exceed the daily allowance and pose a risk to human health.